2008
DOI: 10.1080/10428190802124000
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of orphan receptor tyrosine kinase (ROR1) and Wilms' tumor gene 1 (WT1) in different subsets of B-cell acute lymphoblastic leukemia

Abstract: Recent molecular investigations have demonstrated over-expression of a large number of tumor associated antigens (TAAs) in a variety of malignancies. Over-expression of ROR1 gene, a member of the receptor tyrosine kinase family, has recently been reported in B-cell chronic lymphocytic leukemia. Wilms' tumor gene 1 (WT1) has long been known as a universal TAA expressed in a variety of solid and hematopoietic malignancies. In the present study, the expression profile of ROR1 and WT1 was investigated in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Furthermore, subtype B-precursor ALL showed higher mean values of WT1 mRNA levels than pre-B ALL. This suggests higher levels of WT1 mRNA expression in undifferentiated hematopoietic cells, which is consistent with previous studies that reported higher WT1 mRNA levels in B-precursor ALL than in other subtypes [22,42]. Moreover, intracellular WT1 mRNA levels decreased when K562 cells (a CML-derived cell strain) differentiated into erythroids or megakaryocytes, and when HL60 cells (a promyelocytic leukemia-derived cell strain) differentiated into granulocytes, monocytes, and macrophages via various inducers of differentiation [43,44].…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, subtype B-precursor ALL showed higher mean values of WT1 mRNA levels than pre-B ALL. This suggests higher levels of WT1 mRNA expression in undifferentiated hematopoietic cells, which is consistent with previous studies that reported higher WT1 mRNA levels in B-precursor ALL than in other subtypes [22,42]. Moreover, intracellular WT1 mRNA levels decreased when K562 cells (a CML-derived cell strain) differentiated into erythroids or megakaryocytes, and when HL60 cells (a promyelocytic leukemia-derived cell strain) differentiated into granulocytes, monocytes, and macrophages via various inducers of differentiation [43,44].…”
Section: Discussionsupporting
confidence: 81%
“…18 Accordingly, we observed an inverse correlation between CpG site methylation and expression levels of these genes, with the exception of ARHGAP8. We found that high methylation levels of the tyrosine kinase ROR1, which is differentially expressed in BCP ALL subtypes, 47 contributed to a lower probability of relapse in BCP ALL. The transcriptional regulator NOTCH3, for which high methylation levels contributed to a lower probability of relapse in t(12;21) ALL, is overexpressed in T-ALL cells and has been suggested to interact with IKZF1 (IKAROS) in the leukemogenesis of T-ALL.…”
Section: Bcp All and T-allmentioning
confidence: 90%
“…36,42 ROR1 mRNA and surface protein were found to be strongly expressed in MCL, as well as positivity in marginal zone lymphoma, B-ALL, and a subset of normal B-cell precursors. 43,44 CD200 has an expression profile including CD19 ϩ B cells (normal and malignant), T-cell blasts, follicular dendritic cells, thymocytes, neural tissue, and endothelium. 45 Despite its expression in normal tissue, CD200 is upregulated in CLL, resulting in a down-regulation of the Th1 immune response.…”
Section: Discussionmentioning
confidence: 99%